THE EFFECT OF EXCHANGE RATE, NATIONAL CONSUMPTION, DOMESTIC PRICES, PRODUCTION, CULTIVATED LAND AREA, AND IMPORT TARIFFS ON INDONESIA’S SOYBEAN IMPORT VOLUME - Nadindra Suci Melati; Elpawati; Rizki Adi Puspita Sari (AGRIBUSINESS JOURNAL, 2026)
Indonesia imports more than 1.5 million tons of soybeans annually from various countries, from the United States, Canada, Brazil, Argentina, and Malaysia. The purpose of this study is to analyze the effect of the rupiah exchange rate against the United States dollar (exchange rate), domestic soybean consumption, domestic soybean prices, domestic production, soybean planting area, and import duty tariff policies on the volume of soybean imports in Indonesia in the period 2012-2022.The data were obtained from Central Statistics Agency, Ministry of Agriculture, Ministry of Trade, Bank Indonesia, and UN Comtrade through documentation and literature studies. Data were analyzed descriptively and quantitatively with multiple regression tests, and classical assumption tests were also carried out to ensure the regression model met the criteria for normality, multicollinearity, heteroscedasticity, and autocorrelation. The regression results show that the rupiah exchange rate has a negative coefficient, but is not significant (p-value 0.0912 > 0.05). Domestic consumption also has no significant effect on soybean imports (p-value 0.5651 > 0.05), although it has a positive coefficient. Domestic soybean prices have a negative and significant effect on soybean imports (p-value 0.0322 < 0.05), meaning that an increase in domestic soybean prices will reduce imports. Domestic soybean production and soybean planted area also have a negative and significant effect on soybean import volume (p-value 0.0030 and 0.0171 < 0.05). Import duty tariff policies show a positive and significant effect on soybean imports (p-value 0.0041 < 0.05), where a decrease in import duty tariffs increases soybean imports. Overall, these factors explain approximately 51.6% of the variation in soybean import volume in Indonesia.